PENGELOLAAN BADAN USAHA MILIK DESA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT PERDESAAN KAWASAN PERTAMBANGAN EMAS DI KABUPATEN SUMBAWA BARAT - Ibrahim Ibrahim; Iwan Tanjung Sutarna (Diponegoro University, 2018)
The potential of West Sumbawa Regency in rural gold mining area is very abundant, but has a high level of poverty. The existence of BUMDes as an alternative in developing the potential that has in increasing the income of village and society. This study aims to examine the advantages and disadvantages of the management of BUMDes in improving the welfare of society in rural gold mining area in West Sumbawa regency. This research uses descriptive qualitative approach. Data collection is done in rural gold mining area of West Sumbawa Regency. The location of this research represent 3 (three) sub districts included in gold mining area consist of: District of Jereweh, Maluk and Sekongkang. Data collection techniques used interviews, documentation, and observation with research subjects ie Village Party, BUMDES Management, beneficiary community and related institutions. Data validity using source triangulation techniques.Data analysis using interactive analysis model that is analysis by using data reduction, data display, and verification and conclusion. The results of this study indicate that BUMDES in rural gold mining areas has not been successful in total in improving the village economy and public welfare of the existing units of BUMDES. BUMDES Gold mining areas still have advantages that are: a) easy access to finance and b) improvement of household economy. Weaknesses: a) Human resources managers and b) business plans are low. There needs to be active participation from the community in running the BUMDes program to the economic progress.